2013
DOI: 10.1007/s00520-013-1741-7
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of chemotherapy-induced diarrhoea: a clinical study of intestinal microbiome alterations, inflammation and circulating matrix metalloproteinases

Abstract: We demonstrated that CD is associated with marked changes in intestinal microflora, methanogenic archaea, matrix metalloproteinase and serum levels of NF-κB, IL-1β and TNF. These changes may result in diminished bacterial functions within the gut, altering gut function and initiating intestinal damage, resulting in the onset of diarrhoea. More importantly, these changes may provide clinicians with a possible new target for biomarkers of toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 41 publications
3
91
0
Order By: Relevance
“…We have previously shown that MMPs are upregulated in the gut in a number of preclinical models of chemotherapy-induced GI toxicity [5, 6]. We have also confirmed these findings in a clinical cohort, with upregulated MMP concentrations in the serum of patients treated with standard dose chemotherapy for breast and colorectal cancer [7]. These findings are of clinical importance as MMP inhibitors have been investigated for their anti-tumor activity, both alone and in combination with chemotherapy [8, 9], with data suggesting they may be a valid adjunct to traditional cancer care.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…We have previously shown that MMPs are upregulated in the gut in a number of preclinical models of chemotherapy-induced GI toxicity [5, 6]. We have also confirmed these findings in a clinical cohort, with upregulated MMP concentrations in the serum of patients treated with standard dose chemotherapy for breast and colorectal cancer [7]. These findings are of clinical importance as MMP inhibitors have been investigated for their anti-tumor activity, both alone and in combination with chemotherapy [8, 9], with data suggesting they may be a valid adjunct to traditional cancer care.…”
Section: Introductionsupporting
confidence: 75%
“…Its affinity for MMP-9 and MMP-12 also holds therapeutic potential as these have both been implicated in the pathobiology of GI toxicity. This is particularly the case for MMP-9, which has been shown to increase in the gut following preclinical irinotecan [6, 12], as well as systemically in patients undergoing standard dose chemotherapy [7]. In the case of cancer progression, a number of MMPs have been implicated in cancer progression, invasion, and metastasis, including MMP-2, 9, 11, 12, and 14 [13, 14], with altered expression/activity in the tumor microenvironment, as well as MMP polymorphisms linked with increased susceptibility to various malignancies [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota is critical in regulating the severity of gut toxicity, with increased levels of LPSproducing, gram-negative bacteria correlating with diarrhoea severity (5,30). Comparable levels of major phylogenies (fermicutes, bacteroidetes) were seen in WT and BALB/c-Tlr4 -/-billy mice at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic chemotherapy may also change the gut microbiota in both humans (17) and animal models (18). In cancer patients, microbiota changes have been correlated with gut toxicity (19) and, in some experimental rat models, alleviation of chemotherapy-induced symptoms is observed after administration of probiotics (20)(21)(22). Under germ-free conditions in mice, the response to chemotherapy is either reduced (23) or increased (24).…”
Section: Introductionmentioning
confidence: 98%